2019
DOI: 10.3390/mi10090625
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Precise Grinding of Sapphire Glass Based on Dry Electrical Discharge Dressed Coarse Diamond Grinding Wheel

Abstract: In this paper, in view of low grinding efficiency and poor ground surface quality of sapphire glass, the coarse diamond grinding wheel dressed by dry impulse electrical discharge was proposed to perform efficient and precise grinding machining of sapphire glass. The dry electrical discharge dressing technology was employed to obtain high grain protrusion and sharp micro-grain cutting edges. The influences of grinding process parameters such as wheel speed, depth of cut and feed speed on the ground surface qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Bone drilling and cutting are also widely applied in surgery, especially in trauma, dentistry, and plastic surgery. As is well known in the machining process, the process parameters have great impact on the process quality [23,24]. There are many publications of bone drilling and cutting focusing on the optimization of the process parameters [6,7,[25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Bone drilling and cutting are also widely applied in surgery, especially in trauma, dentistry, and plastic surgery. As is well known in the machining process, the process parameters have great impact on the process quality [23,24]. There are many publications of bone drilling and cutting focusing on the optimization of the process parameters [6,7,[25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…The experiment found that the surface abrasive particles of the diamond grinding wheel after dry pulse discharge dressing were more prominent, and the prominent height was up to 168.5 µm. The dressed wheel can realize e cient grinding of hard and brittle materials [14] . The removal of diamond grinding wheel by copper and iron electrodes through dry discharge were studied and the results showed that the removal of binder by copper electrode was more than that by iron electrode, but the copper electrode was easy to cause abrasive particles to fall off, and the iron electrode had better removal effect on the graphitization of grinding wheel [15] .…”
Section: Introductionmentioning
confidence: 99%